MENGENAL HACKING SEBAGAI SALAH SATU KEJAHATAN DI DUNIA MAYA - Indah Sari (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2023)
AbstractHacking categorized as one of the cybercrime because hacker is a person specialized in programming that can hack a security system in computer or network for a certain purpose. A hacker generally have the knowledge about computer, programming, network, and also hardware. In a cyberworld, hacker is someone which can perform hacking to any device like computer, webcam, smartphone, and router. A hacking that can cause damage to someone is considered as a criminal activity. From this background, the writer elevates two problem from this case. First, why hacking categorized as a cybercrime? Second, how Public Law see hacking as a cybercrime? The kind of typing that the writer uses in this research is descriptive research (describing an object and taking simple conclusion from it) with secondary data and use statute approach, case approach, and conceptual approach. This kind of technique is collected by library researchÂ  and the data will be analyzed qualitatively. As for the study result, it consists of: the writer found how to distinguish hacking criteria that can be categorized as cybercrime dan see hacking from Public Law perspectiveÂ Keywords: Hacking, Hacker, Cybercrime, and Public Law